THE DEVELOPMENT OF SPATIAL DATABASE MANAGEMENT SYSTEM FOR ELDERLY CASE STUDY : KHAEN DONG SUB-DISTRICT, KHAEN DONG DISTRICT, BURIRAM PROVINCE - Wantong, Chalawan; Chodnock, Kanittha; Kitthanarut, Varit; Salukkham, Ekkaluk; Piwpong, Ratchanee; Marangsee, Supaporn; Sangsakda, Piyachon (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2025)
This research is a research and development study using mixed-methods research. The objectives of this research are to develop a spatial database management system (SDBMS) for the elderly in Khaen Dong Sub-district and to assess sample's satisfaction. The sample was purposive sampling, selecting only personnel who are responsible for caring for the elderly and using the SDBMS. Data collection was conducted using focus group discussions, interviews, Global Positioning System (GPS) devices, and closed-ended questionnaires to assess satisfaction, which were calculated as means () and standard deviations (SD). The developed SDBMS consists of a report section, which shows elderly details such as ADL scores, elderly status, chronic diseases, list of caregivers, etc. On the other hand, in the online map section, users can search and update elderly information. The satisfaction assessment results found that users are most satisfied with SDBMS utilization, with the and SD being 4.87 and 0.24, respectively. Following with satisfaction in program design ( = 4.80, SD = 0.39) and program efficiency ( = 4.73, SD = 0.48), respectively.